Association of Axillary Lymph Node Evaluation With Survival in Women Aged 70 Years or Older With Breast Cancer - Luo, Shi-Ping; Zhang, Jie; Wu, Qi-Sen; Lin, Yu-Xiang; Song, Chuan-Gui (Frontiers in Oncology, 2021)
Background Survival in elderly patients undergoing sentinel lymph node biopsy (SLNB) and axillary lymph node dissection (ALND) has not been specifically analyzed. This study aimed to explore the association between different types of axillary lymph node (ALN) evaluations and survival of elderly breast cancer patients. Methods A retrospective cohort study was conducted of invasive ductal breast cancer patients 70 years and older in the Surveillance, Epidemiology, and End Results database (2004-2016). Analyses were performed to compare the characteristics and survival outcomes of patients who received surgical lymph nodes dissection or not. Breast cancer specific survival (BCSS) and overall survival were compared by using Cox proportional hazards regression analysis and propensity score matching (PSM) methods to account for selection bias from covariate imbalance. Results Of the 75,950 patients analyzed, patients without ALN evaluation had a significantly worse prognosis, while there was no significant difference for BCSS between using a sentinel lymph node biopsy (SLNB) or a axillary lymph node dissection (ALND) after adjustment for known covariates [adjusted hazard ratio (HR)=0.991, 95% confidence interval (CI)=0.925-1.062,p=0.800]. In the stratification analyses after PSM, the ALND did not show a significant BCSS advantage compared with SLNB in any subgroups except for the pN1 stage or above. Furthermore, after PSM of the pN1 stage patients, SLNB was associated with a significantly worse BCSS in hormone receptor negative (HR-) patients (HR=1.536, 95%CI=1.213-1.946, p<0.001), but not in the hormone receptor positive(HR+) group (HR=1.150, 95%CI=0.986-1.340, p=0.075). Conclusion In our study, ALND does not yield superior survival compared with a SLNB for elderly patients with pN1 stage HR+ breast cancer. Although our findings are limited by the bias associated with retrospective study design, we believe that in the absence of results from randomized clinical trials our findings should be considered when recommending the omission of ALND for elderly breast cancer patients.